Cardiovascular events and re-stenosis following administration of G-CSF in acute myocardial infarction: systematic review and meta-analysis. Issue 5 (29th August 2007) - Ince, H; Valgimigli, M; Petzsch, M; de Lezo, J Suarez; Kuethe, F; Dunkelmann, S; Biondi-Zoccai, G; Nienaber, C A
Abstract : Background: Because of the recently published results of the MAGIC study there is confusion as to whether administration of granulocyte-colony stimulating factor (G-CSF) after acute myocardial infarction (MI) should be regarded as a potentially harmful treatment. This meta-analysis of appropriate clinical studies is intended to show the impact of G-CSF given after MI on aggravated incidence of coronary re-stenosis or progression of coronary lesions. Methods: We used a fixed effects model based on the Mantel-Haenszel method to combine results from the different trials. These studies provided the basis for the current analysis comprising 106 patients of whom 62 were subjected to G-CSF treatment. Results: Minimum lumen diameter (MLD) measured immediately after percutaneous coronary intervention (PCI) was similar in both groups with a diameter stenosis of 12.3% (SD 9.5%) in the G-CSF group and 10.3% (8.5%) in the control group (p = 0.32). At follow-up, both MLD and percentage stenosis were not different between G-CSF-treated and control patients. Subsequently, averaged late lumen loss revealed similar results and no differences between groups (p = 0.11), and neither stent thrombosis nor re-infarction in either group. Conclusions: The current meta-analysis of clinical reports fails to justify an elevated risk for coronary re-stenosis after PCI in acute MI or adverse events following G-CSF in the setting of MI when used after state of the art treatment in carefully conducted clinical protocols.